From digital drawing to dissemination of the collected data, reflections on the virtual creative process - Ylenia Ricci; Andrea Pasquali; Stéphane Giraudeau (Revista de Expresión Gráfica en la Edificación, 2021)
The research presented here focuses on the understanding of the act of drawing not only as a means of restitution of the architectural survey but also considering the modernization of the representation techniques. This must be considered as a first step for the creation of virtual environments capable of offering advanced methodologies for the dissemination of the collected data. Expanding the techniques that can be referred to drawing will not only be a necessary process, and one that is already underway, but it will have to strengthen the intrinsic potential of representation. The aim is to communicate and record information with common codes facilitating reading and dissemination. Central to this is the use of drawing as a means of connection between different figures researching a topic. Drawing must be interpreted as the restitution and result of processes of elaboration and codification of the information collected with the survey, that leads us to the modeling and realization of exhaustive elaborations, containing the greatest amount of information useful for the dissemination of the existing architectural heritage and beyond. Its digital evolution, an opportunity to increase the potential and strength of the scientific dissemination of knowledge.